Plasma Thrombin Assay using a Chromogenic Substrate in Disseminated Intravascular Coagulation due to Snake Bite Envenomation - Herrmann, R P; Bailey, P E (Thrombosis and Haemostasis, 1979)
Using the chromogenic substrate, Tos-Gly-Pro-Arg-pNA-HCL (Chromozym TH, Boehringer Mannheim) plasma thrombin was estimated in six cases of envenomation by Australian elapid snakes. All patients manifested findings chracteristic of defibrination due to envenomation by these snakes. Fibrin-fibrinogen degradation products were grossly elevated, as was plasma thrombin in all cases.Following treatment with antivenene, all abnormal coagulation parameters returned rapidly towards normal by 24 hours and plasma thrombin disappeared.